Glacial geomorphology and chronology in the Selamiut range / Nachvak fiord area, Torngat Mountains, Labrador - Evans, D. J. A. (1984)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1984. Geography Bibliography : leaves 117-121.